A Millimetre-wave Probe for Fast Screening and Evaluation of Corrosion in Planar Conductors: Numerical Simulations. (June 2019) - Li, Wenjia; Li, Yong; Tan, Jianguo; Abidin, Ilham Mukriz Zainal; Hu, Jinhua; Chen, Zhenmao; Wu, Yongzhuo
Abstract: Planar conductors are commonly used in critical mechanical structures. Due to high-temperature and high-pressure environment, corrosion may occur in in-service planar conductors, and seriously threatens structural integrity and safety. Hence, it is indispensable to detect and evaluate corrosion using Non-destructive Testing (NDT) techniques before structural failure. As a technique complementary to other Electromagnetic NDT methods, Microwave NDT is found to be advantageous in terms of high efficiency and accuracy in inspection of conductors subject to surface flaws. In this paper, a millimetre-wave probe for efficient detection and evaluation of corrosion in planar conductors is proposed and intensively investigated via simulation. A 3D Finite Element (FE) model of the proposed probe is established based on electromagnetic wave theory. The characteristics of the microwave propagation along with the mechanism regarding corrosion detection are intensively analysed. The probe structure and parameters are subsequently optimised in an effort to enhance the detectability, sensitivity and accuracy in corrosion evaluation. Besides, signal processing techniques involving extraction of features from the S-parameter in the function of frequency are investigated.